Principal's strategy in managing new student admissions in vocational high schools - Muhammad Muliya Al-Amien; Achadi Budi Santosa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
Implementation of strategic management is believed to have a major influence on the achievement of institutional goals. This study aims to reveal the principal's strategy in implementing strategic management in the New Student Admissions (PPDB) program in Bantul district. Using a qualitative approach, this study selected the principal, and the PPDB team, as the main sources of information. Data collection techniques were carried out through interviews, observation, and document review. The results of the study revealed that the management strategy of PPDB SMK in Bantul district was carried out through: 1) Strategic Environmental Analysis, including; the advantages of the school, the economic background of the prospective student, geographical location, family background, and the origin of the prospective student's school. 2) Strategy Formulation, including; school promotion teams, fees, collaboration between institutions, strong partnerships between schools and the world of industry, relevance of majors based on prospective students' areas, to the clarity of information provided by the school. 3) Strategy implementation, including: increasing teacher and employee commitment, cost transparency, involvement of students and parents, ease of registration, excellent service, and promotional programs. 4) Evaluation and monitoring, periodically observing the level of interest of the registrants, and the level of achievement of targets. The implementation of PPDB's strategic management has not been carried out consistently, as a result, only a few schools have benefited from the implementation of this strategy.